2018
DOI: 10.3892/ijmm.2018.4012
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone induces reactive oxygen species‑mediated apoptosis in human rheumatoid arthritis fibroblast‑like synoviocytes

Abstract: The present study investigated the mechanisms of apoptosis induced by cryptotanshinone (CT) in human rheumatoid arthritis fibroblast-like synoviocytes (RA-FLSs). Cell Counting kit-8 assay was performed to determine the cytotoxic effects of CT in human RA-FLSs, including primary RA-FLS, HFLS-RA and MH7A cells, and in HFLS cells derived from normal synovial tissue. Annexin V-FITC/PI staining was used to detect the apoptotic effects of CT in HFLS-RA and MH7A cells. Flow cytometry was performed to detect the apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Cryptotanshinone (CPT), an active compound isolated from Radix Salviae Miltiorrhizae , has been reported to possess diverse pharmacological activities, including anti-fibrosis, neuroprotective, anti-inflammatory, anti-atherosclerotic, and antioxidant activities ( Mei et al, 2009 ; Wong et al, 2010 ; Ran et al, 2016 ; Lo et al, 2017 ; Bai et al, 2019 ; Sun et al, 2019 ; Zhou et al, 2019 ). For example, CPT reduced inflammation and oxidative stress in renal interstitial fibrosis by modulating the Nrf-2/HO-1 and NF-kappaB signaling pathways ( Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptotanshinone (CPT), an active compound isolated from Radix Salviae Miltiorrhizae , has been reported to possess diverse pharmacological activities, including anti-fibrosis, neuroprotective, anti-inflammatory, anti-atherosclerotic, and antioxidant activities ( Mei et al, 2009 ; Wong et al, 2010 ; Ran et al, 2016 ; Lo et al, 2017 ; Bai et al, 2019 ; Sun et al, 2019 ; Zhou et al, 2019 ). For example, CPT reduced inflammation and oxidative stress in renal interstitial fibrosis by modulating the Nrf-2/HO-1 and NF-kappaB signaling pathways ( Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these encouraging discoveries on its cardio-protective role, we assumed that CTS might have a therapeutic effect on preventing the occurrence of CME, and our results demonstrated that pretreatment of CTS for 2 weeks could effectively improve cardiac function and injury in CME rats. (Zhu et al, 2019), and CTS also reduced ROS-mediated apoptosis in human synoviocytes (Sun et al, 2019). Of note, considering that CME significantly elevated oxidative stress and cell apoptosis, both of which play important roles in the process of CME, that is why we evaluated oxidative stress and apoptosis in our study.…”
Section: Discussionmentioning
confidence: 88%
“…We hypothesized that the decrease in adipogenesis may be related to increased ROS‐induced adipocyte cell dysfunction in shPrx2‐3T3‐L1 cells. Several studies have reported that excessive ROS generation leads to cell death, resulting in weaken cellular functions (Hampton & O'Connor, 2016; H. N. Sun et al, 2018; F. Zhang, Xie, Munoz, Lau, & Monks, 2014). We explored the expression of markers involved in cell death after adipogenesis and found that expression levels of cleaved caspase‐3 and cleaved PARP (cell death markers) were markedly increased in shPrx2‐3T3‐L1 cells, while 3T3‐L1 cells only showed a slight increase by the 8th day (Figure 4a,b).…”
Section: Resultsmentioning
confidence: 99%